PROGRAM KALENDER MASEHI DENGAN WETON MENGGUNAKAN VISUAL BASIC .NET - khoirur_rozikin; Nuris Dwi Setiawan; Unang Achlison (Elkom : Jurnal Elektronika dan Komputer, 2023)
A calendar is a system for naming a period of time and is known as a Calendar Date. The Gregorian calendar is used throughout the world including Indonesia, this calendar is calculated from the birth of Jesus from Nazareth, the calculation uses the pattern of the sun's movement. The Gregorian calendar has 12 months in a year and 7 days in a week. The Hijri calendar is a calendar system based on the circulation of the moon around the earth, called Hijiriah because of its first year when the migration of the Prophet Muhammad from Mecca to Medina took place in 662 AD. Due to the different intervals or repetitions between the day and the weton where the day will return to the same day after 7 days while the weton will return to the same weton after 5 days, it is quite difficult to find out the day and weton on a certain date that is hundreds or thousands of days apart from the current date. The Gregorian calendar program with weton is used to find out the day and weton of a date by specifying the month and year, a 1 month calendar will be displayed along with the day and weton